Econometric Policy Evaluation: Note - Cooley, Thomas F.; LeRoy, Stephen F.; Raymon, Neil (American Economic Review, 1984)
for successive values of the endogenous variables y,, with the x, treated as deterministic forcing variables. Here 0 is a parameter vector and the Et are random shocks. Lucas correctly observed that such a formulation is inconsistent with a view of agents as optimizers: except in special cases in which the future is irrelevant to present decisions, it makes no sense to think of agents as optimizing if they know that their budget constraints are liable to shift arbitrarily (i.e., in a way which is not characterized probabilistically) as government policy changes. Lucas was led to augment the foregoing equation by adding to the system a government policy function